Strength Analysis of Rollers and Supports of A Hydraulic Dynamometer Chassis Using Finite Element Method - Bagaskoro, Satria; Aryadi, Widya (Universitas Negeri Semarang, 2024)
The measuring performance tool of electric motorcycle in Indonesia is limited, which in contrast to the rapid development of motorcycle technology. Therefore, this study aims to develop a chassis hydraulic dynamometer as a tool to measure the mechanical parameters of electric motorcycles This research was conducted using an experimental method based on simulations with SolidWorks 2022 software as the simulation tool for roller and support strength. Simulation was performed on variations 35 mm, 40 mm, and 45 mm shaft diameter roller, using AISI 1045 steel material. Based on calculations and simulation results, a roller with a 35 mm shaft diameter can withstand the applied external load with a maximum von Mises stress of 2,394 x 108 N/m2², a maximum strain of 7,283 x 10-4, a maximum displacement of 6,275 x 10-2 mm, and a minimum safety factor of 2.2. Based on calculations and simulation results, the roller with a 35 mm shaft diameter is safe, optimal, and efficient in terms of material usage. Therefore, a roller with a 35 mm shaft diameter and SKF UCP 207 support was selected for use on the chassis hydraulic dynamometer